The PD-1/PD-L1 (B7-H1) Pathway in Chronic Infection-Induced Cytotoxic T Lymphocyte Exhaustion. (25th September 2011) - Hofmeyer, Kimberly A.; Jeon, Hyungjun; Zang, Xingxing
Abstract : Cytotoxic CD8 T lymphocytes (CTLs) play a pivotal role in the control of infection. Activated CTLs, however, often lose effector function during chronic infection. PD-1 receptor and its ligand PD-L1 of the B7/CD28 family function as a T cell coinhibitory pathway and are emerging as major regulators converting effector CTLs into exhausted CTLs during chronic infection with human immunodeficiency virus, hepatitis B virus, hepatitis C virus, and other pathogens capable of establishing chronic infections. Importantly, blockade of the PD-1/PD-L1 pathway is able to restore functional capabilities to exhausted CTLs and early clinical trials have shown promise. Further research will reveal how chronic infection induces upregulation of PD-1 on CTLs and PD-L1 on antigen-presenting cells and other tissue cells and how the PD-1/PD-L1 interaction promotes CTLs exhaustion, which is crucial for developing effective prophylactic and therapeutic vaccination against chronic infections.